The dynamic interplay between context and the language learner - King, Jim 1974- (Palgrave Macmillan, 2016)
"Traditionally dominant approaches in applied linguistics have tended to emphasise cognitive aspects of second language acquisition, and have placed the language learner as being largely independent from the context. This volume offers a timely challenge to this notion by bringing together a state-of-the-art collection of chapters which acknowledge that learner characteristics and behaviour are in fact dynamic and can be influenced by a multitude of competing temporal and situational factors. An international team of scholars (based in Austria, China, Germany, Hong Kong, Japan, the United Kingdom and the United States) specialising in a range of language learning-related disciplines contribute cutting edge conceptual papers and data-based studies, making this book essential reading for graduate students, researchers and second language practitioners with an interest in psychological and social aspects of language learning. Chapter authors include Jim Askham, Vera Busse, Letty Chan, Joseph Falout, Glenn Fulcher, Alex Gilmore, Michael Handford, Maiko Ikeda, Jim King, Sarah Mercer, Satomi Nakahira, Jian-E Peng, Agneta Svalberg, Florentina Taylor and Tomoko Yashima. Diane Larsen-Freeman's Foreword sets the scene"..